A Ruptured Cornual Ectopic Pregnancy at 17 Weeks Gestation: A Case Report - Khan, MI; Nyeer, R; Laila, R; Jahan, S (BIRDEM Medical Journal, 2014)
Cornual pregnancy is a specific variety of ectopic gestation which occurs in the rudimentary horn of the uterus. It often rupture later than other tubal pregnancies because the myometrium is more distensible than the fallopian tube. Traditionally, the treatment is cornual resection (removal of rudimentary horn) or hysterectomy where the pedicle is short and the attachment is wide. Here, we report a case where cornual pregnancy was diagnosed at 17 weeks of gestation after uterine rupture and profound haemorrhage. The patient underwent laparotomy followed by cornual resection with salpingectomy. DOI: http://dx.doi.org/10.3329/birdem.v4i1.18558 Birdem Med J 2014; 4(1): 50-51